Compliance of the POCT method with the fully automated method for HbA1c determination - Milinković, Neda; Sarić Matutinović, Marija; Dmitrašinović, Gordana; Ignjatović, Svetlana (Archives of Pharmacy, 2022)
Previous research suggests that point-of-care (POCT) determination of glycated hemoglobin (HbA1c) is a diagnostic test that can be an adequate alternative to measuring HbA1c in the laboratory. The main goal of this study was to examine the analytical characteristics of the novel INCLIX POCT method for HbA1c determination in order to test its performance before introducing this method into routine use. HbA1c is measured in a duplicate in 44 EDTA blood samples parallel on INCLIX POCT device (Sugitech, Inc.) and using automated turbidimetric immunoinhibition test on Olympus AU400 (Beckman Coulter). The within run imprecision was 7.58%, between runs imprecision was 6.63% and 6.22%, and day-to-day imprecision was 8.80% and 7.51%. Total laboratory imprecision was in agreement with those stated by the manufacturer. A statistically significant Pearson correlation coefficient was calculated (r = 0.871, P < 0.01; linear R2 = 0.757). Using Deming regression analysis, the following equation was obtained: y = -1.80 + 1.304x. Our results indicate statistically significant correlation, linear relationship, and a significant degree of compatibility between the two analyzed methods. However, the negative bias of the HbA1c values determined on the POCT analyzer compared to the Olympus AU400 was confirmed, highlighting the need to standardize the INCLIX method.
Keywords: HbA1c; POCT; diabetes; Deming regression